2022
DOI: 10.1037/edu0000706
|View full text |Cite
|
Sign up to set email alerts
|

Why do students use strategies that hurt their chances of academic success? A meta-analysis of antecedents of academic self-handicapping.

Abstract: Self-handicapping is a maladaptive strategy that students employ to protect their self-image when they fear or anticipate academic failure. Instead of increasing their effort, students may harm their chances of success by procrastinating, strategically withdrawing effort, or engaging in destructive behaviors like drug abuse, so that potential failure can be attributed to these handicaps rather than to stable personal characteristics (e.g., low intelligence). A large body of research has focused on potential an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 117 publications
(232 reference statements)
5
25
2
Order By: Relevance
“…That is, with students' social networks, their academic self-handicapping increases. These findings are consistent with the empirical findings of researchers such as Uysal and Knee (2012), Callan et al (2014), Fadhli et al (2021), Vrij et al (2021), Funkhouser and Hallam (2022), Schwinger et al (2022).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…That is, with students' social networks, their academic self-handicapping increases. These findings are consistent with the empirical findings of researchers such as Uysal and Knee (2012), Callan et al (2014), Fadhli et al (2021), Vrij et al (2021), Funkhouser and Hallam (2022), Schwinger et al (2022).…”
Section: Discussionsupporting
confidence: 92%
“…Research showed a positive relationship between the use of virtual social networks and self-regulatory learning strategies and the components of self-regulatory learning strategies (cognitive and metacognitive strategies). Theobald (2021) and Schwinger et al (2022) also conclude that social media can facilitate the creation of personal learning environments and enable teachers to implement and develop selfregulatory learning processes such as setting appropriate personal goals, using work strategies to manage information, and engaging in self-monitoring. Self-assessment contributes to the advancement of social knowledge.…”
Section: Path Coefficients T-value P-value Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results not only confirm these results, but also show that even a very brief mindset induction that took only a few minutes can make a salient difference in the self-handicapping behavior of the vulnerable students with more of a fixed mindset, while such manipulation had less impact on those students who are protected by higher level of prior growth mindset. Additionally, these results are in line with assumptions of Schwinger et al 43 showing the effectiveness of even a very brief emotional-motivational manipulation that could reduce the level of self-handicapping.…”
Section: Discussionsupporting
confidence: 90%
“…Self-handicapping is a form of active self-sabotaging that people perform to establish specific external events as excuses if subsequent performance fails. Thus, rather than forgetting or postponing preparatory behaviors, self-handicapping implies a tendency to engage in strategically delayed behaviors that protect self-esteem (e.g., Strube, 1986 ; Schwinger et al, 2021 ). For example, staying up late the night before an important exam may later be used as an excuse if the exam results are not as positive as expected.…”
Section: Factors Associated With Procrastination and How They Align W...mentioning
confidence: 99%